STEAM Practices to Explore Ancient Architectures Using Augmented Reality and 3D Printing with GeoGebra - Bedewy Shereen El; Choi Kyeongsik; Lavicza Zsolt; Fenyvesi Kristof; Houghton Tony (De Gruyter, 2021)
In this study, we develop mathematical educational practices for students to explore ancient buildings using GeoGebra, Augmented Reality and 3D printing. It is an interdisciplinary approach, intertwining history, culture, mathematics, and engineering. For example, the 3D modelling of Cheomseongdae in Korea and the Temple of Dendera in Egypt can enable students to practice a multimodal set of traditional and innovative learning approaches. Students might use their mathematical knowledge to reflect on architectural and cultural history in a modeling task.